Aspects and clinical procedures of eruptive changes of permanent upper canines - Sheila Marcia Francisco; Mario Cappellette Junior (Dental Press Editora, 2012)
INTRODUCTION: Even though the upper canine is the tooth that presents most eruption anomalies, after the third molars, canine retention prevalence in the population is quite low. Local, physiologic and pathologic factors can provide difficulties for the tooth eruptive process. The correct diagnosis in trying to prevent upper canine retention with ectopic eruption is fundamental to choose the ideal treatment, which can be performed by various methods. OBJECTIVE: The present paper has the purpose of approaching aspects related to impacted upper permanent canines by a literature review, including localization and treatment conducts.